Chromosome level genome assembly of ‘Wanfeng’ almond (Prunus dulcis) - Dongdong Zhang; Zhenfan Yu; Xingyue Liu; Yong Li; Bin Zeng; Lirong Wang (Scientific Data)
Abstract We assembled a chromosome-level genome of Chinese native ‘Wanfeng’ almond, with a size of 288.53 Mb and a contig N50 of 30.48 Mb. Approximately 270 Mb (93.58%) of the sequences are anchored on 8 Superscaffolds, and 174.59 Mb (60.51%) of the sequences are repetitive sequences. BUSCO assessment revealed that the ‘Wanfeng’ almond genome assembly included 99.3% complete BUSCOs. A total of 24,230 protein-coding genes were annotated, and 24,033 were functional. The assembly of the ‘Wanfeng’ almond genome provides a valuable genetic resource for molecular breeding of native almonds in China.